Handbook of carbon-based nanomaterials - Thomas, Sabu; Sarathchandran, C., 1978-; Ilangovan, S. A.; Moreno-Pirajan, Juan Carlos (Micro & nano technologies., 2021)
Handbook of Carbon-Based Nanomaterials provides a comprehensive overview of carbon-based nanomaterials and recent advances in these specialized materials. This book opens with a brief introduction to carbon, including the different forms of carbon and their range of uses. Each chapter systematically covers a different type of carbon-based nanomaterial, including its individual characteristics, synthesis techniques and applications in industry, biomedicine and research. This book offers a broad handbook on carbon-based nanomaterials, detailing the materials aspects, applications and recent advances of this expansive topic. With its global team of contributing authors, Handbook of Carbon-Based Nanomaterials collates specific technical expertise from around the world, for each type of carbon-based nanomaterial. Due to the broad nature of the coverage, this book will be useful to an interdisciplinary readership, including researchers in academia and industry in the fields of materials science, engineering, chemistry, energy and biomedical engineering.